2011
DOI: 10.1542/peds.2010-3428
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide in Preterm Infants: A Systematic Review

Abstract: There was a 7% reduction in the risk of the composite outcome of death or BPD at 36 weeks for infants treated with iNO compared with controls but no reduction in death alone or BPD. There is currently no evidence to support the use of iNO in preterm infants with respiratory failure outside the context of rigorously conducted randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 31 publications
5
83
0
2
Order By: Relevance
“…Систематические наблюдения и мета-анализ подтвердили эффективность использования NO для снижения смертности новорожденных [53]. NO часто применяют при лечении недоношенных детей для предотвращения развития бронхолегочной дисплазии [54,55]. Оксид азота оказался среди агентов с потен-циальным эпигенетическим эффектом, оказывающим свое действие на экспрессию генов через реакцию нитролизации [56].…”
Section: вопросы современной педиатрииunclassified
“…Систематические наблюдения и мета-анализ подтвердили эффективность использования NO для снижения смертности новорожденных [53]. NO часто применяют при лечении недоношенных детей для предотвращения развития бронхолегочной дисплазии [54,55]. Оксид азота оказался среди агентов с потен-циальным эпигенетическим эффектом, оказывающим свое действие на экспрессию генов через реакцию нитролизации [56].…”
Section: вопросы современной педиатрииunclassified
“…A recent case series indicates that iNO may reduce established BPDassociated pulmonary hypertension to a greater degree than oxygen alone [31]. On the other hand, large clinical trials have shown inconsistent benefit when iNO is used to prevent BPD [32][33][34][35].…”
Section: Nitric Oxidementioning
confidence: 99%
“…A recent case series indicates that iNO may reduce established BPDassociated pulmonary hypertension to a greater degree than oxygen alone [31]. On the other hand, large clinical trials have shown inconsistent benefit when iNO is used to prevent BPD [32][33][34][35].Outside of the NICU setting, the most common clinical use of iNO is for the infant or child with congenital heart disease with associated pulmonary hypertension. Postoperatively, iNO is frequently used to prevent or treat pulmonary hypertensive crises, improve oxygenation, and increase cardiac output.…”
mentioning
confidence: 99%
“…Grisafi et al (10) showed that amniotic fluid stem cells delivered intratracheally can restore partly alveolarization and angiogenesis in an adult rat model of hyperoxia lung injury. Although stem cell therapy is a promising novel therapy for vascular injury-related diseases, studies have demonstrated that only a small portion of transplanted cells can home to the target (11,12).Previous studies suggest that impaired nitric oxide (NO) production may contribute to the pathogenesis of BPD (13,14), and that administration of NO (inhaled NO or NO donor) can improve lung vascular and airspace structure in newborns or BPD models (15)(16)(17). However, the reasons that NO improves lung structures are not well defined, a likely hypothesis is that NO promotes angiogenesis (18).…”
mentioning
confidence: 99%
“…Previous studies suggest that impaired nitric oxide (NO) production may contribute to the pathogenesis of BPD (13,14), and that administration of NO (inhaled NO or NO donor) can improve lung vascular and airspace structure in newborns or BPD models (15)(16)(17). However, the reasons that NO improves lung structures are not well defined, a likely hypothesis is that NO promotes angiogenesis (18).…”
mentioning
confidence: 99%